Acquired brain injury, social work and the challenges of personalisation - Holloway, Mark; Fyson, Rachel (Oxford University Press, 2015)
Increasing numbers of adults in the UK are living with acquired brain injury (ABI), with those affected requiring immediate medical care and longer-term rehabilitative and social care. Despite their social needs, limited attention has been paid to people with ABI within the social work literature and their needs are also often overlooked in policy and guidance. As a means of highlighting the challenge that ABI presents to statutory social work this paper will start by outlining the common characteristics of ABI and consider the (limited) relevant policy guidance. The particular difficulties of reconciling the needs of people with ABI with the prevailing orthodoxies of personalisation will then be explored, with a particular focus on the mis-match between systems which rest on presumptions autonomy and the circumstances of individuals with ABI - typified by executive dysfunction and lack of insight into their own condition. Composite case studies, drawn from the first author’s experiences as a case manager for individuals with ABI, will be used to illustrate the arguments being made. The paper will conclude by considering the knowledge and skills which social workers need in order to better support people with ABI.